Persistent Octahedral Coordination in Amorphous GeO_{2} Up to 100 GPa by Kβ^{′′} X-Ray Emission Spectroscopy - G. Spiekermann; M. Harder; K. Gilmore; P. Zalden; Ch. J. Sahle; S. Petitgirard; M. Wilke; N. Biedermann; C. Weis; W. Morgenroth; J. S. Tse; E. Kulik; et al. (Physical Review X, 2019)
We measure valence-to-core x-ray emission spectra of compressed crystalline GeO_{2} up to 56 GPa and of amorphous GeO_{2} up to 100 GPa. In a novel approach, we extract the Ge coordination number and mean Ge-O distances from the emission energy and the intensity of the Kβ^{′′} emission line. The spectra of high-pressure polymorphs are calculated using the Bethe-Salpeter equation. Trends observed in the experimental and calculated spectra are found to match only when utilizing an octahedral model. The results reveal persistent octahedral Ge coordination with increasing distortion, similar to the compaction mechanism in the sequence of octahedrally coordinated crystalline GeO_{2} high-pressure polymorphs.